Design of English Learning Application for Children Early Childhood - Saputra, Very Hendra; Pasha, Donaya; Afriska, Yolanda (Proceeding International Conference on Science and Engineering, 2020)
Early childhood development includes several aspects such as physical, motor, language, social and cognitive. Cognitive factors are important role because most learning activities are always related to thinking and remembering problems. Besides language development is very important, it is because language is a communication tool of children with their environment, with good communication it will result in good interactions. Therefore, children need to be given the right stimulus so that during the child's growth and development to the maximum. One stimulus that can be given for cognitive development and language of early childhood is by providing an interesting medium, because in the development of early childhood the way of thinking requires visualization of abstract thinking. The purpose of this research is to design an application of learning English for mobile-based early childhood which is expected to be used as an \alternative as a medium to assist cognitive development and communication of early childhood. English based learning applications for mobile children are made with Construct 2 software. The development method uses the Multimedia Development Life Cycle. While testing the application using ISO 9126, the results of testing the quality of the application using ISO 9126 which includes the Functionality and Usability characteristics obtained Functionality test results obtained value of 100%, and the Usability test results obtained value of 91.11% so it can be concluded that the design of English learning applications is appropriate to be used as a medium to assist cognitive development and communication of early childhood.